A retrospective study: cardiac MRI of fulminant myocarditis in children—can we evaluate the short-term outcomes? - Wang, Haipeng; Zhao, Bin; Jia, Haipeng; Gao, Fei; Zhao, Junyu; Wang, Cuiyan (PeerJ, 2016)
Background Fulminant myocarditis (FM) is an inflammatory disease of the myocardium that results in ventricular systolic dysfunction and causes acute-onset heart failure. Cardiac magnetic resonance (CMR) has become the primary noninvasive tool for the diagnosis and evaluation of myocarditis. The aim of our study was to assess the CMR findings at different course of FM and the short-term outcomes of fulminant myocarditis (FM) in children. Methods Eight FM children with CMR examinations were included in our study. Initial baseline CMR was performed 10 days (range, 7–20 days) after onset of FM and follow-up CMR after 55 days (range, 33–75 days). Cardiac morphology and function and myocardial tissue characterization at baseline and follow-up CMR were compared using paired T-test and Mann–Whitney U test. The clinical data and initial CMR findings were also compared to predict short-term outcomes. Results The median age of eight FM children was 8.5 years old (range, 3–14). The initial CMR findings were most common with early gadolinium enhancement (EGE, 100%), followed by signal increasing on T2WI and late gadolinium enhancement (LGE, 87.5%), increased septal thickness (75.0%) and increased left ventricle ejection fraction (LVEF, 50.0%). Only three LGE (37.5%), one signal increasing on T2WI (12.5%) and one increased LVEF (12.5%) were found at follow-up. Statistically significant differences were found between initial and follow-up CMR abnormalities in the septal thickness, left ventricular end-diastolic diameter (LVEDD), end-systolic volume (ESV), LVEF, left ventricular mass, T2 ratio and LGE area (P = 0.011, P = 0.042, P = 0.016, P = 0.001, P = 0.003, P = 0.011, P = 0.020). The children with full recovery performed higher incidence of III° atrioventricular block (AVB, five cases VS 0 case) and smaller LGE area (104.0 ± 14.5 mm2 VS 138.0 ± 25.2 mm2) at baseline CMR. Discussion The CMR findings of FM in children were characteristic and useful for early diagnosis. Full recovery of clinical manifestations, immunological features and CMR findings could be found in most FM children. The presence of III° AVB and smaller LGE area at baseline CMR might indicate better short-term outcomes.
Keywords: Cardiac magnetic resonance; Children; Fulminant myocarditis; Short-term outcomes